The Role and Deficiency of Zinc Mineral in Immune System - Widhyari, Sus Derthi (Indonesian Bulletin of Animal and Veterinary Sciences, 2012)
Zinc (Zn) is a micro mineral which is needed by every cell in the body. Adequate Zn mineral is important in maintaining optimal health. Zn functions as a cofactor of various enzymes, structural integrity of cells, DNA synthesis, hormonal storage and release,  immunotransmision  and  immune  system.  Zn  deficiency causes  decreased  appetite,  dermatitis,  growth  retardation, delayed sexual maturation, infertility and imunodeficiency. This is associated with changes in the function of immune system response, such as decreased B and T cell functions, reduced phagocytosis and decreased cytokine production. Severe Zn deficiency is characterized by severely depressed immune function and frequent infections. Zn enhances immune function for specific and non-specific immunity. The role of non-specific immune respone is through the activity of cells phagocytosis by neutrophils and monocytes, while the specific immune response can be humoral and cellular mediated by lymphocytes B and T. Supplementation of Zn can improve the activity of leukocyte cells through stimulating the production of tumor necrosis factor- alpha (TNF-α) by monocytes cells, thereby increasing the ability of phagocytosis. In addition, Zn is also able to increase the production of lymphokines that cause lymphocyte cells able to differentiate and proliferate.   Key words: Zn, deficiency, immunity, leucocyte cells